Caffeinated chewing gum enhances maximal strength and muscular endurance during bench press and back squat exercises in resistance-trained men - Ding, Li; Liu, Jue; Yao, Yi; Guo, Li; Chen, Bin; Cao, Yinhang; Girard, Olivier (Frontiers in Nutrition, 2025)
IntroductionCaffeinated chewing gum, known for its rapid absorption, has not been previously studied for its effects on maximal strength and muscular endurance in resistance exercise. The aim of this study was to determine the efficacy of caffeinated chewing gum on maximal strength and muscular endurance during bench press and back squat exercises.MethodsIn a randomized, double-blind design, 16 resistance-trained males (age: 21.6 ± 2.0 years, height: 176.8 ± 6.1 cm, mass: 79.6 ± 8.8 kg) chewed either caffeinated gum (3 mg/kg) or a placebo gum on two occasions, 1 week apart. After a standardized warm-up, participants chewed the gum for 5 min before performing maximal strength test (one-repetition maximum [1RM]) and muscular endurance test (60% 1RM repetitions to failure) for bench press and back squat exercises. 1RM, number of repetitions, ratings of perceived exertion and pain perception were assessed.ResultsCaffeinated chewing gum significantly improved 1RM in both bench press (105.3 ± 14.5 vs. 100.3 ± 13.4 kg, +5.0% [95% confidence interval (CI): 3.7–6.3%], p < 0.01) and back squat (172.3 ± 20.2 vs. 161.9 ± 22.3 kg, +6.8% [95%CI: 4.1–9.5%], p < 0.01) exercises with small effect size (Cohen’s d: 0.36 [95%CI: 0.09–0.63] and 0.49 [95%CI: 0.22–0.76], respectively), despite similar levels of pain perception and RPE (p > 0.05). It also increased the number of repetitions in both bench press (20 ± 5 vs. 17 ± 4, +18.8% [95%CI: 11.5–26.1%], p < 0.01) and back squat (37 ± 11 vs. 28 ± 8, +33.3% [95%CI: 23.1–43.4%], p < 0.01) exercises with moderate-to-large effect size (Cohen’s d: 0.76 [95%CI: 0.48–1.03] and 0.89 [95%CI: 0.60–1.16], respectively), despite similar levels of pain perception and RPE (p > 0.05).DiscussionCaffeinated chewing gum (3 mg/kg) improved both maximal strength and muscular endurance during bench press and back squat exercises in resistance-trained men. This approach offers a practical and time-efficient method to improve training performance while minimizing the risk of side effects.